Intimacy in Illegality : Experiences, Struggles and Negotiations of Migrant Women - Bartolini, Flaminia (Kultur und soziale Praxis., 2021)
How do migrant women living in illegality build intimate relationships? How do they experience, resist or take advantage of the tight link between intimacy and migration status created by the German migration legislation?Drawing on rich biographical accounts and ethnographic methods, the book offers an insightful and sensitive look at a mostly unknown aspect of life in illegality. Adopting a critical feminist perspective, Flaminia Bartolini shows how intimacy should be understood in its intrinsic power dimension and looks critically at the German migration regime and on its effects on migrants' lives.